Rajendra Prasad’s Terminal Chop: New Technique For Full Thickness Nuclear Segmentation in Hard Cataract - Rajendra Prasad; Anurag Badhani; Geetika Badhani (Delhi Journal of Ophthalmology)
‘Direct chop’ has become the procedure of choice in hard cataracts but is still fraught with incomplete cracks and difficult instrument manipulation. We describe a new technique, ‘Terminal Chop’ for full thickness nuclear segmentation in hard cataract. A short, shallow, central trench is sculpted in the central nucleus, the phaco tip is engaged at the distal end of the trench and impaled into the nucleus, keeping the tip directed towards the equator parallel to the pupillary plane within the superficial layers of the nucleus. Equator of the nucleus is then slightly lifted vertically and brought out at the capsulotomy edge. A specially designed blunt tipped chopper is then simply passed around the lens equator and hooked. A small full thickness nick is created adjacent to the phaco tip using a blunt chopper. With a firm grip of the nucleus at the equator, lateral separation of the 2 instruments is initiated to create a vector force of 90 degrees, splitting the entire nucleus from equator to equator through the centre, into two complete clean halves. Direction of splitting follows the cleavage plane through the lens fibres thus causing minimal trauma.